2010
DOI: 10.1007/s12011-010-8700-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Trace Elements during Follicular Atresia in Goat (Capra hircus) Ovary

Abstract: Quantitative analysis of follicular fluid and granulosa cells from small, medium and large antral atretic follicles of goat (Capra hircus) ovaries was conducted to study the alterations in trace elements viz zinc (Zn), copper (Cu), manganese (Mn), and iron (Fe). The zinc content was lower in the follicular fluid (0.993 ± 0.001, 0.935 ± 0.002, 1.321 ± 0.001 μg/ml) and granulosa cells (0.867 ± 0.002, 0.801 ± 0.001, 1.073 ± 0.002 μg/mg) of small, medium, and large antral atretic follicles respectively than their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Our work demonstrated the prevalence of several autophagic genes in AcHE1b expressing atretic oocytes. Since AcHE s are localized in the inner periphery of the chorion, and autophagic genes are specifically expressed in cell organelles, we presumed that some intermediary ion channel 9, 40 or chemical cue (possibly responsive to different AcHE concentrations) is crucial for the induction of autophagy. Reversion of AcHE1b OV related autophagic effect by intracellular Zn +2 ion chelator, further strengthens the above hypothesis and also suggests that AcHE1b might be essential for zinc ion mediated autophagy maintenance in oocytes 4143 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our work demonstrated the prevalence of several autophagic genes in AcHE1b expressing atretic oocytes. Since AcHE s are localized in the inner periphery of the chorion, and autophagic genes are specifically expressed in cell organelles, we presumed that some intermediary ion channel 9, 40 or chemical cue (possibly responsive to different AcHE concentrations) is crucial for the induction of autophagy. Reversion of AcHE1b OV related autophagic effect by intracellular Zn +2 ion chelator, further strengthens the above hypothesis and also suggests that AcHE1b might be essential for zinc ion mediated autophagy maintenance in oocytes 4143 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the addition of calcium (Ca +2 ) increased the germ cell survivability in medaka, reared at HT (unpublished data). The involvement of trace elements in autophagy 8, 9, 40 and fewer cAMP-dependent protein kinase phosphorylation sites 37 in AcHE1b , suggests that the HE s differentially trigger the uni/bidirectional ion flow and influence the cell elimination fate. Due to the differential steroid responsive transcription of AcHE , it is acceptable to assume that apoptosis/autophagy cell fate decision greatly depends on the alternatively splicing of HEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumption of alcohol has always been part of daily life in many societies and it will always continue to be so in the future. However, the World Health Organization has shown that alcohol intake represents the third largest risk factor for disease burden especially in highincome countries, behind only hypertension and smoking, both of which are also related to alcohol misuse [9]. Ethanol is among one of the most widely abused drug which can both suppress reproductive function and sexual behavior as observed in laboratory animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Copper (Cu) is essential trace element to maintaining the functioning of living organisms (Yunus et al, 2015). In in vitro studies, it was reported that potential use of Cu as atretic marker and for fertility improvement plans (Bhardwaj and Sharma, 2011). It was also reported that complexes of copper (Cu 2+ ) with gonadotropin-releasing hormone (GnRH) are even more effective in the release of luteinizing hormone (LH) than native GnRH (Michaluk and Kochman, 2007).…”
Section: Introductionmentioning
confidence: 99%